The Epistemology of Rasa as a Basic Foundation of the Javanese Psychology - Aryaning Arya Kresna (PT FORMOSA CENDEKIA GLOBAL, 2023)
This paper is an attempt to comprehend the epistemology of the Javanese worldview when it is used as the primary argument for indigenous psychology. The aim is to explore epistemology in Javanese psychology as a cultural understanding framework for the concept of knowledge and human experience. Javanese psychology is rooted in the rich Javanese tradition and philosophy, which have a unique way of understanding the universe and human existence in it. The method in this paper is literature research using the Wilhelm Dilthey hermeneutic method. The first step is describing the influence of positivism. The next steps are to discuss the concepts of metaphysics and epistemology in Rasa, and the reasons why indigenous psychology should be built upon the foundation of congruent philosophical thoughts. The conclusion that can be drawn is that the concept of Rasa will become the basis of the epistemological foundation of a new branch of indigenous psychology called Javanese psychology.